The Administrative Judge and European Convention guaranteed rights for Human Rights Protection - Jean Massot (Zbornik Radova Pravnog Fakulteta u Splitu, 2012)
In the historical development of the French administrative judge several moments in time have been differentiated. The first period was from 1947-1989 where court decisions were very rarely based on Convention provisions. The second period started October 20, 1989 with the court decision in the Nicolo case. Administrative adjudication process accepted, after the above mentioned decision, to supervise the harmonisation of national law with the Convention. The Government Council carefully dared at the beginning and later more frequently to implement such supervision of harmonisation. This brought about not just forbidding the application of the law due to contrariness to the Convention, but to also to suing the state for damages which occurred from such law, particularly when the legislator ignored some directions. In the third period the Government Council, after much resistance, harmonised with Strasbourg Court legal practise. On the other hand, it seems that it has a significantly more restrictive concept of the obligation of independence, impartiality, and prescribing obligations that the court has to be legally regulated both in system of bodies and in dispute settlement by the European Court for the protection of human rights and fundamental freedoms.